Comparison of antioxidant activity and some bioactive compounds between Anise and citrus Syrian honey - Al-Haql, Mohammed Yousef; Habbal, Hoda Yasein; Yakoub, Wafaa Asaad (Journal of agricultural, environmental and veterinary sciences, 2021)
The aim of this research was to estimate and compare the antioxidant activity, total phenolic content, total flavonoids, amino acid proline, diastase activity and Hydroxymethylfurfural (HMF) in both Anise and citrus Syrian honey. 24 honey samples were collected directly from beekeepers during the harvest season of 2019. There were 12 samples of anise honey from Hama, Aleppo and Damascus countryside governorates. Moreover, another 12 citrus honey samples from Lattakia and Tartous governorates. Chemical tests were performed on samples directly after the collection. The analysis achieved in the laboratories of the Department of Food Sciences - Faculty of Agriculture - Damascus University, Damascus, Syria. The results demonstrate that the means of anti-oxidant activity were (45.58 & 24.05), total phenolic content (98.28 & 37.14 mg GAE/100g), total flavonoids (23.77 & 24.66 mg QE/100g), proline (876.74 & 396.38mg/kg), diastase activity (32.38 & 12.51 Gothe), and HMF contents (10.11&2.06 mg/kg) in both anise and citrus honey, respectively. The statistical study showed that there were significant differences (P <0.05) in all the studied Parameters between one type of honey samples as well as between the two types of honey. Anise Syrian honey shows better antioxidant activity, total phenolic content, total flavonoids, proline and diastase activity than citrus honey. However, citrus honey is distinguished by its low content of HMF and its high content of total flavonoids.